MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING DALAM PENINGKATAN AKHLAK SISWA PADA PELAJARAN PENDIDIKAN AGAMA ISLAM DI ACEH - Saputra, Fedry; Saputra, Aidil; Efendi, Sumardi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
This study examines the impact of implementing the Contextual Teaching and Learning (CTL) model on improving students’ moral character in Islamic Religious Education (PAI) lessons in Aceh. The research was conducted in several public and private junior high schools in Aceh Barat, Aceh Selatan, Banda Aceh, Aceh Besar, Pidie, and Bireuen. This study aimed to evaluate the effectiveness of CTL in enhancing students’ understanding and application of moral values. The research employed a field study approach with a qualitative methodology. Data were collected through observations, in-depth interviews with PAI teachers and students, and an analysis of school documents. The findings indicate that the implementation of the Contextual Teaching and Learning (CTL) model has a significantly positive impact on improving students’ moral character, particularly in aspects of honesty, responsibility, and social care, while also helping students connect Islamic Religious Education (PAI) material with real-life situations. This provides practical contributions to the development of contextual-based learning in Islamic character education. The study concludes that the CTL model improves students’ moral character in PAI lessons. It is recommended that schools in Aceh consider adopting this model more broadly to achieve holistic educational goals